2014
DOI: 10.1055/s-0034-1368243
|View full text |Cite
|
Sign up to set email alerts
|

Three-Day Combination Treatment for Vulvovaginal Candidosis with 200 mg Clotrimazol Vaginal Suppositories and Clotrimazol Cream for the Vulva is Significantly Better than Treatment with Vaginal Suppositories Alone – an Earlier, Multi-Centre, Placebo-Controlled Double Blind Study

Abstract: !Problem: According to the guidelines, acute vulvovaginal candidosis (VVC) may be treated vaginally, through a combination of vaginal treatment and cream for the vulva or orally. However, there is a lack of investigations into whether combined treatment for the vagina and vulva achieves better results than vaginal treatment alone. Method: In 1999, 160 patients with vulvovaginal candidosis from ten German gynaecological practices were included in a study and treated on a randomised basis with three 200 mg clotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Similarly, the single use of clotrimazole 10% internal cream or clotrimazole 500 mg ovule (soft capsule) yielded mycological cure rates that were comparable to those following a single dose of clotrimazole 500 mg vaginal tablet. In cases of vulvar involvement, the combined use of intravaginal clotrimazole and external clotrimazole cream provided more favorable treatment results than intravaginal clotrimazole alone [ 22 ]. In all studies, topical clotrimazole was well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the single use of clotrimazole 10% internal cream or clotrimazole 500 mg ovule (soft capsule) yielded mycological cure rates that were comparable to those following a single dose of clotrimazole 500 mg vaginal tablet. In cases of vulvar involvement, the combined use of intravaginal clotrimazole and external clotrimazole cream provided more favorable treatment results than intravaginal clotrimazole alone [ 22 ]. In all studies, topical clotrimazole was well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…206 Based on the above, intravaginal administration of antifungals is recommended for vulvovaginal candidiasis. [195][196][197][198][199][200][201][202][203][204][205][206] CQ19: IS A TOPICAL ANTIFUNGAL AGENT RECOMMENDED FOR TINEA VERSICOLOR TREATMENT?…”
Section: Cq17: Is a Topical Antifungal Agent Recommended For Vulvovagmentioning
confidence: 99%
“…Recently, Mendling et al performed a comparative study on 160 patients with VVC in which they compared treatment with clotrimazole vaginal suppositories alone and a combination of 2% clotrimazole cream for external use and clotrimazole vaginal suppositories. They concluded that the combination of both was better than the suppositories alone (19).…”
Section: Treatment Of Uncomplicated Vulvovaginal Candidiasismentioning
confidence: 99%